36=(6x+1)/(x-6)

Simple and best practice solution for 36=(6x+1)/(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=(6x+1)/(x-6) equation:


D( x )

x-6 = 0

x-6 = 0

x-6 = 0

x-6 = 0 // + 6

x = 6

x in (-oo:6) U (6:+oo)

36 = (6*x+1)/(x-6) // - (6*x+1)/(x-6)

36-((6*x+1)/(x-6)) = 0

(-1*(6*x+1))/(x-6)+36 = 0

(-1*(6*x+1))/(x-6)+(36*(x-6))/(x-6) = 0

36*(x-6)-1*(6*x+1) = 0

30*x-217 = 0

(30*x-217)/(x-6) = 0

(30*x-217)/(x-6) = 0 // * x-6

30*x-217 = 0

30*x-217 = 0 // + 217

30*x = 217 // : 30

x = 217/30

x = 217/30

See similar equations:

| X^2-5x-36=4x | | X^3=-2x^2+8x | | (X+5)/4=-7 | | 16=(6x+1)/(x-1) | | X^2+3x+6=-2x | | X^3=-2x+8x | | 3(2x+1)(x-3)=0 | | 6/46x23/30/-2/10 | | 9u-u= | | 18t=6+6(4t+11) | | y-4.73=7.4 | | r-9.2=-6.8 | | 5x^2-3x+4=x^2-3x+13 | | (x+5)/4=7 | | c+20=15 | | 42=2w+8 | | k(2)+2k-71=9 | | d/20=9 | | k/4=-15 | | Xy-5y-2x+10= | | -6w=108 | | 8x^3y^2+27y^2= | | 6x-30=x-x+4 | | n-20=-19 | | 14x^2-5=0 | | -7+ln(3x)=4 | | 5x^2y^3(3x^2+xy+4y)= | | (s+2)+2s=8 | | -120x+3000=1500 | | -160x+4000=2500 | | 10y-15=0 | | 7x+1-3x-8= |

Equations solver categories